Rhythm perception, production, and synchronization during the perinatal period - Provasi, Joëlle; Anderson, David I.; Barbu-Roth, Marianne (Frontiers in Psychology, 2014)
Sensori-motor synchronization (SMS) is the coordination of rhythmic movement with an external rhythm. It plays a central role in motor, cognitive, and social behavior. SMS is commonly studied in adults and in children from four years of age onward. Prior to this age, the ability has rarely been investigated due to a lack of available methods. The present paper reviews what is known about SMS in young children, infants, newborns, and fetuses. The review highlights fetal and infant perception of rhythm and cross modal perception of rhythm, fetal and infant production of rhythm and cross modal production of rhythm, and the contexts in which production of rhythm can be observed in infants. A primary question is whether infants, even newborns, can modify their spontaneous rhythmical motor behavior in response to external rhythmical stimulation. Spontaneous sucking, crying, and leg movements have been studied in the presence or absence of rhythmical auditory stimulation. Findings suggest that the interaction between movement and sound is present at birth and that SMS can be observed in special conditions and within a narrow range of tempi, particularly near the infant’s own spontaneous motor tempo. The discussion centers on the fundamental role of SMS in interaction and communication at the beginning of life.